2023
DOI: 10.1039/d2ya00134a
|View full text |Cite
|
Sign up to set email alerts
|

Towards an accelerated decarbonization of the chemical industry by electrolysis

Abstract: Electrochemical technologies support the transition towards carbon-neutral chemical manufacturing and we need new approaches to accelerate electrolysis scale-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…In contrast to frequently deployed H-cells, where the electrochemical materials (cathodes and anodes) are immersed in liquid solutions, flow reactors provide an opportunity to expose the electrochemical materials to a well-controlled interphase with an intensified mass transfer, ultimately allowing electrochemical reactions to be conducted in a more controlled manner. This enables, e.g., a more selective synthesis of specific hydrocarbons [16] , [17] , [18] . Besides CO 2 electrolysis and hydrogen evolution, flow reactors can also be deployed for nitrogen reduction and many chemical reactions relevant to fine and pharmaceutical engineering applications [19] .…”
Section: Hardware In Contextmentioning
confidence: 99%
“…In contrast to frequently deployed H-cells, where the electrochemical materials (cathodes and anodes) are immersed in liquid solutions, flow reactors provide an opportunity to expose the electrochemical materials to a well-controlled interphase with an intensified mass transfer, ultimately allowing electrochemical reactions to be conducted in a more controlled manner. This enables, e.g., a more selective synthesis of specific hydrocarbons [16] , [17] , [18] . Besides CO 2 electrolysis and hydrogen evolution, flow reactors can also be deployed for nitrogen reduction and many chemical reactions relevant to fine and pharmaceutical engineering applications [19] .…”
Section: Hardware In Contextmentioning
confidence: 99%
“…For a few decades, certain industrial applications have employed water electrolysis to make hydrogen, but in recent years, interest in this process has grown as a result of rapidly developing technology and the accessibility of inexpensive power. [143][144][145] Many predictions for the future of hydrogen generation rely heavily on electrolysis, but other developing technologies, such thermolysis and photolysis, may allow for a more effective use of thermal or solar energy.…”
Section: Hydrogen Transportationmentioning
confidence: 99%
“…Electrochemical reduction of carbon dioxide presents major advantages among the established CO 2 conversion approaches, such as output tunability with applied voltage and utilization of renewable energy as the process driving force. , High-temperature (>700 °C) operation endows solid oxide electrolyzer cells for carbon dioxide electrolysis (CO 2 –SOECs) with favorable thermodynamics and fast electrode kinetics, resulting in unrivaled performance over lower-temperature technologies, in terms of obtainable current density and energy efficiency. , A schematic of the working principles of a CO 2 –SOEC is reported in Scheme S1 of the Supporting Information. At the current state, SOECs for CO 2 conversion have reached the “market uptake” technological readiness level and are available as units and pilot plants. , It has been recently reported that CO 2 –SOECs approaching the commercialization stage ensured durability exceeding a year on stream, marking the difference with the lower-temperature CO 2 conversion devices, still at the early stage of development . Nevertheless, issues must be faced to achieve commercialization on a wider scale, mostly involving SOEC electrode material performance on the long distance, and device stability. The benchmark materials for the CO 2 –SOEC anodes and cathodes are Mn- or Co-containing perovskite oxides and Ni-YSZ cermets, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…At the current state, SOECs for CO 2 conversion have reached the "market uptake" technological readiness level and are available as units and pilot plants. 5,6 It has been recently reported that CO 2 −SOECs approaching the commercialization stage ensured durability exceeding a year on stream, marking the difference with the lower-temperature CO 2 conversion devices, still at the early stage of development. 7 Nevertheless, issues must be faced to achieve commercialization on a wider scale, mostly involving SOEC electrode material performance on the long distance, and device stability.…”
Section: ■ Introductionmentioning
confidence: 99%